Patient-cost studies on self-administered treatment (SAT) for drug-sensitive tuberculosis compared to facility-based directly observed treatment, short-course (DOTS): a protocol for a systematic review - Carmen Sue Christian; Yonela Faith Ndlangalavu (BMJ Open)
Introduction Many patients with tuberculosis (TB) suffer from a huge economic burden, even though TB services are often provided free of charge at the point of care. Costs can create significant barriers, hindering patients’ access to TB treatment. These costs include direct medical costs (such as consultation fees), direct non-medical costs (such as transportation costs) and indirect costs (such as wages foregone). This systematic review aims to synthesise the best available evidence on economic evaluations of patient-cost studies on self-administered treatment (SAT) for drug-sensitive TB compared with facility-based directly observed treatment, short-course (FB DOTS), globally.Methods and analysis We will conduct a systematic review following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guidelines and search PubMed, Academic Search Complete, Scopus, CINAHL Plus (EBSCO) and Google Scholar for articles published up to 2025, without date restrictions. Eligible studies must be full or partial (cost analyses without effectiveness data) economic evaluations conducted globally, comparing SAT to FB DOTS regarding TB patient costs. Grey literature will be included. Exclusion criteria include studies not reporting patient costs between SAT and FB DOTS, and non-economic evaluations (non-original research). Two independent reviewers will conduct the screening, data extraction and quality assessment. A quality assessment will be performed using the Consolidated Health Economic Evaluation Reporting Standards statement, the Consensus on Health Economic Criteria checklist and the ROBINS-I tool.Ethics and dissemination Ethics approval is not required for this systematic review because it does not use individual patient data. Instead, we will use publicly available economic evaluation research studies. Findings will be presented at international and national conferences and published in open-access, peer-reviewed journals. PROSPERO registration number CRD42024591221.